Machiny miotające w kampaniach Aleksandra Macedońskiego = Throwing machines in the campaigns of Alexander of Macedon - Suszczenia, Paweł (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
The text is a polemic with the discourse image of the development stage of catapults in the times of Alexander the Great. This image assumes the existence of developed throwing machines capable of destroying fortifications at the time in question. However, the analysis of the descriptions of the use of siege machines contained in the text, undermines this picture, and at the same time proposes solutions to several problematic issues.
Keywords: Aleksander Wielki (356-323); Vitruvius; catapults; oxybeles; siege engine; Tyre; Witruwiusz; katapulty; oksybeles; machiny oblężnicze; Tyr